Could measuring factors other than a lack of financial resources help in achieving the zero hunger goal - Hyink, Jillian; McFadden, Brandon R.; Phipps, Brandy E.; Gundersen, Craig (Frontiers in Sustainable Food Systems, 2024)
The second Sustainable Development Goal of Zero Hunger, defined by the United Nations, broadly focuses on several dimensions of food access and availability, including measures of hunger and undernourishment, food insecurity, and malnutrition. Progress toward the Zero Hunger goal is monitored using indicators like the Prevalence of Undernourishment and the prevalence of moderate or severe food insecurity. These indicators are widely regarded as accurately portraying the underlying phenomena of concern. There are, however, other considerations one may want to include when considering the broader food system, including the role of food access and sovereignty in the rural areas of low-income countries. This paper reviews measurements of food insecurity and reflects on how food access and sovereignty may improve food security and, conversely, how it may impede advances toward alleviating food insecurity. These considerations can be helpful in tracking the need and progress toward the Sustainable Development Goal of Zero Hunger.